2014
DOI: 10.26719/2014.20.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' knowledge, attitude and practices regarding management of medications in Ramadan

Abstract: To evaluate knowledge, attitude and practices (KAP) of physicians regarding the management of medications in Ramadan we used a self-administered questionnaire on a target sample of 381 physicians

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…Individuals with chronic diseases are recommended to receive advice from healthcare professionals about fasting during Ramadan. However, it is emphasized that a majority of the fasting patients did not voluntarily visit the doctor for consultation immediately before Ramadan and all efforts must be made to have them visit the clinic before starting fasting 10 . In a study conducted with cancer patients, it was observed that 54.3% wanted advice on fasting 25 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals with chronic diseases are recommended to receive advice from healthcare professionals about fasting during Ramadan. However, it is emphasized that a majority of the fasting patients did not voluntarily visit the doctor for consultation immediately before Ramadan and all efforts must be made to have them visit the clinic before starting fasting 10 . In a study conducted with cancer patients, it was observed that 54.3% wanted advice on fasting 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is scientifically accepted that religion and spirituality have an important effect on the physical and mental health of individuals, it may be ignored by healthcare professionals. Further, in a study that investigated knowledge, attitude and practices of doctors about drug management during Ramadan, it was seen that they had a significant lack of knowledge about proper drug management 10 . Healthcare professionals should respect the religious practices of their patients and guide them properly so they may fulfill such practices safely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This needs to be resolved and clarified to patients. Muslim jurists, scholars of religion, medical practitioners, pharmacologists, and specialists in other human sciences agree unanimously that some administration routes do not nullify fasting, such as drugs administered through injection into the skin, muscles, joints, or veins (with the exception of intravenous feeding) [ 3 , 18 , 19 ]. Therefore, given that participant responses indicate the belief that insulin injection nullifies fasting, physicians, participant educators, and religious leaders should clarify appropriate administration routes that do not constitute as nullification of fasting.…”
Section: Discussionmentioning
confidence: 99%